Morphometrics of Swimming Crabs (Portunus pelagicus) in Lombok Waters - Supiani, Lilik; Karnan , Karnan; Ilhamdi, Mohammad Liwa (Jurnal Biologi Tropis, 2026)
Crab catches that do not meet standards have the potential to disrupt the population structure and reduce the size of the catch, so morphometric information is important as a basis for sustainable management and utilization; moreover, in Lombok waters, morphometric reference data is declared unavailable, while regulations also stipulate a prohibition on catching females laying eggs and the size of the carapace width is suitable for catching >10 cm. This study aims to analyze the morphometric characteristics of Portunus pelagicus crabs landed in Teluk Ujung (n=75) using a descriptive-exploratory approach to describe the size distribution. The results showed that harvested swimming crabs had weight range of 47-87 g (60%), a carapace width of 10-11 cm (24%), a total carapace width of 13–14 cm (19%), and a carapace length of 6-7 cm (27%). The parameters of the appendix also vary, including the width of the claw prop 2-3 cm (74%), the length of the prop 10-11 cm (15%), the height of the propous 1-2 cm (57%), the length of the claw dactylus 4-5 cm (29%), the width of the claw of 1-2 cm (57%), the length of the claw of 5-6 cm (29%), the width of the 4th leg of the claw 0.5-1 cm (74%), the length of the 4th leg of the claw 2-3 cm (50%), the width of the dactylus of the swimming leg 1-2 cm (72%),  Length of the dactylus of the swim leg 2-3 cm (73%), the width of the abdomen 1-2 cm (41%), the length of the telson 0.5-1 cm (59%). These findings present size profiles as basic data on local stocks as well as enrichment materials for zoology learning, and can be used to strengthen more selective fishing practices and are in line with the provisions of catchable size.